2010
DOI: 10.1177/0363546510385398
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral Transtibial Posterior Cruciate Ligament Reconstruction Combined With Anatomical Reconstruction of Posterolateral Corner Insufficiency

Abstract: In this series, double-bundle PCL reconstruction combined with posterolateral corner reconstruction did not appear to have advantages over single-bundle PCL reconstruction combined with posterolateral corner reconstruction with respect to the clinical outcomes or posterior knee stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 34 publications
2
73
0
5
Order By: Relevance
“…20,21 Studies using the Lysholm test found no significant between-group difference in outcome (n ¼ 372; Figure 3). 9,[21][22][23][24][26][27][28][29] Those reporting the Tegner activity scale indicated significantly better outcomes after doublerather than single bundle reconstruction (n ¼ 247; OR À0.34, 95% CI À0.68, 0.00; Figure 4). 9,[21][22][23]26 The IKDC examination was reported in five studies (n ¼ 222) [20][21][22][23]28 with outcomes categorized as grade A or grades C/D (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…20,21 Studies using the Lysholm test found no significant between-group difference in outcome (n ¼ 372; Figure 3). 9,[21][22][23][24][26][27][28][29] Those reporting the Tegner activity scale indicated significantly better outcomes after doublerather than single bundle reconstruction (n ¼ 247; OR À0.34, 95% CI À0.68, 0.00; Figure 4). 9,[21][22][23]26 The IKDC examination was reported in five studies (n ¼ 222) [20][21][22][23]28 with outcomes categorized as grade A or grades C/D (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the paucity of high level evidence supporting double versus single bundle reconstruction, a recent large cohort study failed to demonstrate a difference in the clinical and functional outcome between the two techniques [8]. There is also a lack of prospective studies supporting superiority of transtibial versus tibial inlay techniques; the evidence available suggests satisfactory results in both approaches and choice is often due to surgeons experience [10].…”
Section: Discussionmentioning
confidence: 99%
“…There is also a lack of prospective studies supporting superiority of transtibial versus tibial inlay techniques; the evidence available suggests satisfactory results in both approaches and choice is often due to surgeons experience [10]. According to the available literature, better results with double bundle tibial inlay PCL reconstruction are only found in multiligaments injury cases [5,8]. Chamfering the sharp edges of the bone at the entrance of the tunnels in our experience helps reduce risk of reconstruction failure by graft abrasion without the need to alter the graft position angulation or tibial tunnel route suggested in other studies [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies supporting this idea utilized conventional static uniplanar testing to assess stability in the ligament-deficient and reconstructed state. However, clinical studies evaluating PCL and PLC reconstruction [17,20,36,39] have failed to demonstrate a correlation between the degree of knee laxity measured by uniplanar testing and subjective outcomes.…”
Section: Introductionmentioning
confidence: 99%